U-Pb zircon geochronology, geochemistry and Nd isotopic study of Neoproterozoic bimodal volcanic rocks in the Kangdian Rift of South China: implications for the initial rifting of Rodinia - Li, Zheng-Xiang; Kinny, Peter (Elsevier Science BV, 2002)
SHRIMP U-Pb zircon age, geochemical and Nd isotopic data are reported for the Neoproterozoic Suxiongvolcanic rocks in the Kangdian Rift, western South China. These volcanic rocks are bimodal, consisting mainly of mildly alkaline basalts and trachydacites to rhyolites. SHRIMP U-Pb zircon age determination indicates that theywere erupted at 80312 Ma. Most basaltic rocks are characterized by high positive Nd(T) values (+5 to +6),pronounced enrichment in Th, Ta, Nb, LREEs, Sr, P, Zr, Hf, Ti, smooth LREE-enriched patterns and generally 'humped' trace element spidergrams. They resemble the alkali basalts of the Hawaiian oceanic island basalts (OIB)and the Ethiopian continental flood basalts (CFB). These features suggest that the basaltic rocks were most probably derived from an OIB-like mantle source without appreciable crustal/lithospheric contamination. Differentiated basalt and trachyandesite samples show relatively low Nd(T) values (+1.7 to +2.4) and Nb-Ta depletion due to contamination by the mafic lithosphere and/or crustal materials. The rhyolite and dacite samples have small positive Nd(T) values (+1.1 to +2.6), general enrichment in most incompatible trace elements (K, Rb, Th, Zr, Hf and REEs) but significant depletion in Nb, Ta, Sr, P, Eu and Ti. They share geochemical characters of A2-type granites, and are likely generated by shallow (P4 kbar) dehydration melting of hornblende-bearing granitoids. Geochemical and Nd isotopic characters and high-volcanicity of the Suxiong bimodal volcanic successions are consistent with their formation in a continental rift environment, such as the Ethiopian rift. The Kangdian Rift is considered as part ofa wider continental rift system produced by a starting mantle plume beneath South China during the Neoproterozoic breakup of Rodinia.